Re-Thinking Gender, Artivism and Choices. Cultures of Equality Emerging From Urban Peripheries - Moura, Tatiana; Cerdeira, Linda (Frontiers in Sociology, 2021)
Gender dimensions of violence, and especially women’s experiences in settings of urban violence have been the subject of important feminist research, including those that highlight gender as essential for comprehensive analyses of security and urban violence, and for promoting solutions and positive change. A primary contribution of feminist research indeed has been to demonstrate that there are both visible and invisible aspects of urban violence. A gap in literature on these gender dimensions is that of men’s construction of masculinities – and how these constructions are challenged during times. An important set of invisible phenomena within urban spaces and their peripheries includes the positive and decolonial responses that occur, including non-violent and feminist cultural and artistic pathways and the factors that lead men to resist to dominant, violent, or ‘hyper’ versions of masculinities. While there is a predominate focus on men’s involvement in violence, far less attention has been placed on men’s non-violent pathways. Based on examples of cultural, artistic and activist practices from the peripheries, namely those emerging in Rio de Janeiro, this article aims to discuss how artivism can challenge gender inequalities and power relations.